IMPLEMENTASI TRANSAKSI NON TUNAI DALAM PENGELOLAAN KEUANGAN DI BKPSDM KABUPATEN JAYAPURA - Kory, Kory; Marlissa, Elsyan R.; Aedah, Nur (Universitas Cenderawasih, 2023)
This study aims to determine the process of implementing a non-cash transaction system for regional financial management. The main objective of this research is to analyze and explain the obstacles to the Implementation of Non-Cash Transaction Policies in Financial Management at the Personnel and Human Resources Development Agency (BKPSDM) of Jayapura Regency, as well as to analyze and explain the supporting and inhibiting factors for the Implementation of Non-Cash Transaction Policies in Financial Management in Agencies. Staffing and Human Resource Development (BKPSDM) Jayapura Regency. This research is a type of qualitative research. The data sources in this study are primary data sources and secondary data sources. Primary data was obtained by direct interviews with competent parties at BKPSDM Jayapura Regency. Secondary data is used to support primary data in the form of materials and data archives from the Jayapura Regency BKPSDM. Data was collected using interviews, documentation and observation. The results showed that Policy Implementation, in terms of the Communication aspect, namely that most of the employees in the finance section already understood the implementation of Non-Cash Transactions, then in terms of the Resource aspect with Non-Cash Transactions there was little difficulty in carrying it out, then in terms of the Disposition aspect that The treasurer is expected to have more expertise and skills in carrying out his duties and functions, and in terms of the Bureaucratic Structure aspect, based on the informants' responses, it is known that the Bureaucratic Structure indicator is good enough. The supporting factor is the existence of strong support for the successful implementation of Non-Cash Transactions in the ranks of regional heads as decision makers to policy implementers. While the Inhibiting Factors there are still deficiencies in the implementation of non-cash transactions, so that employees do not fully understand the Non-Cash Transaction System and some people still do not understand because the socialization has not been thorough.